Proceedings of the 2nd International Conference on Intervention and Applied Psychology (ICIAP 2018) 2019
DOI: 10.2991/iciap-18.2019.90
|View full text |Cite
|
Sign up to set email alerts
|

Cultural contact, cultural values, and education for life and work as predictors of future orientation in the Baduy community

Abstract: Future orientation is a cognitive construct that explains the future orientation of individuals, especially the younger generation, to anticipate general events. Because education is responsible for the foundation of a sustainable future in a society, government and society need to prepare their younger generation through formal education. But this is not the case with the Baduy indigenous people. Although the government provides formal education for every ethnic group in Indonesia, the Baduy community rejects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Another study indicated that graduates of English Literature Study Program, Sultan Agung Islamic University expressed confidence in future encounters since they were equipped with Islamic academic culture in which Islamic values had been implanted in the students' overall behavioural attitudes (Nurhamidah, 2018). Still another study showed that students trained with Islamic accountability were more accepted when studying overseas in Islam-based countries resulting in easier much cultural adjustment than those without such a training prior to departure (Mulyadi, Prabowo, & Chrisnatalia, 2019). The previous studies on Islamic values indicated that chances for such values to be implemented in different settings and purposes are still wide-open.…”
Section: It Is Argued Thatmentioning
confidence: 99%
“…Another study indicated that graduates of English Literature Study Program, Sultan Agung Islamic University expressed confidence in future encounters since they were equipped with Islamic academic culture in which Islamic values had been implanted in the students' overall behavioural attitudes (Nurhamidah, 2018). Still another study showed that students trained with Islamic accountability were more accepted when studying overseas in Islam-based countries resulting in easier much cultural adjustment than those without such a training prior to departure (Mulyadi, Prabowo, & Chrisnatalia, 2019). The previous studies on Islamic values indicated that chances for such values to be implemented in different settings and purposes are still wide-open.…”
Section: It Is Argued Thatmentioning
confidence: 99%